Fine-scale analysis of edge effect of shrub patch in different grassland types - Wang, Ning; Jing, Yupeng; Ren, Xiaomeng; Qiao, Hui; Zhang, Huimin; Dang, Xiaohong; Meng, Zhongju (Frontiers in Environmental Science, 2022)
Boundaries may have important effects on landscape patterns, landscape change mechanisms, and dynamic processes. However, little is known about the dynamic mechanism of patch boundary changes at a fine scale. To elucidate the characteristics of grassland patches at fine scales and to provide a reference for the mechanism of change and development direction of patchy landscapes. In this paper, the patch of different grassland types in Xilingol League was studied by NMDS, RDA, and SEM methods, to analyze the vegetation community and soil characteristics of surface soil and the relationship between them: The changes in soil vegetation community and soil characteristics were completely different among the three grassland types, and the abrupt changes of vegetation index and soil properties were different. Vegetation index mostly ranged from −1 m to 0 m, and soil index mostly ranged from −0.5 m to 1 m. Fine-scale vegetation and soil boundaries are well defined, vegetation boundaries are mostly between −1 and 0 m and soil boundaries are mostly between −0.5–1 m, and soil properties have a clear influence on plant characteristics. The difference in organic matter, nitrogen, and phosphorus content is an important factor affecting the change of patch boundary, the distribution of the RDA results showed that the organic matter, nitrogen and phosphorus contents in all three grasslands explained >70% of the environmental factors. The emergence of annual vegetation involves a process of succession, specifically, the nature of the underlying soil determines the type of plants at the boundary. The dynamic characteristics of the soil-plant mutual-feed mechanism determine the location and variation of patch boundaries to adapt to disturbance states. The results of this study provide insight into how boundaries respond to changes in environmental conditions and drive dynamic changes at the landscape level.